2020
DOI: 10.1002/ece3.6702
|View full text |Cite
|
Sign up to set email alerts
|

Species complex diversification by host plant use in an herbivorous insect: The source of Puerto Rican cactus mealybug pest and implications for biological control

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 89 publications
3
23
0
Order By: Relevance
“…Closely related species of herbivorous insects with overlapping distribution ranges can be considered good candidates of ecological speciation by means of divergent selection (Nosil, 2012). In this context, the roles of mating timing (Santos et al, 2007), endosymbiotic infections (Frati et al, 2004), and host plant associations (Poveda-Martinez et al, 2020;Prowell, McMichael, & Silvain, 2004) have been reported and referred to as processes shaping the fate of co-occurring species. Other processes, such as introgression following interspecific hybridization, may also play an important role in young sympatric species (Martin et al, 2013;Tonzo, Papadopoulou, & Ortego, 2020;Valencia-Montoya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Closely related species of herbivorous insects with overlapping distribution ranges can be considered good candidates of ecological speciation by means of divergent selection (Nosil, 2012). In this context, the roles of mating timing (Santos et al, 2007), endosymbiotic infections (Frati et al, 2004), and host plant associations (Poveda-Martinez et al, 2020;Prowell, McMichael, & Silvain, 2004) have been reported and referred to as processes shaping the fate of co-occurring species. Other processes, such as introgression following interspecific hybridization, may also play an important role in young sympatric species (Martin et al, 2013;Tonzo, Papadopoulou, & Ortego, 2020;Valencia-Montoya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…atacamensis , or vice versa, was an important driver of genetic divergence between populations. However, these sampling sites are separated by ~500 km, suggesting that isolation by distance may also have played a role in differentiation (Forbes et al, 2017; Hood et al, 2020; Poveda‐Martínez et al, 2019, 2020). Indeed, correlation and multiple regression analyses stressed the roles of both host plants and geographic distance as drivers of genetic divergence within C .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study of population genetic structure patterns in sympatric and allopatric populations of recently diverged species can provide information on the processes that drive diversification at the intraand interspecific levels and the mechanisms maintaining species boundaries.Closely related species of herbivorous insects with currently overlapping distributions could have arisen via ecological speciation through divergent selection (Nosil, 2012) or in allopatry followed by secondary contact. In the case of ecological speciation, the roles of mating timing (Santos et al, 2007), endosymbiotic infections (Frati et al, 2004), and host plant associations (Prowell et al, 2004;Poveda-Martínez et al, 2020) have been reported as processes shaping the fate of co-occurring species. In contrast, allopatric speciation, a common mode of speciation, does not necessarily imply divergent selection, unlike sympatric speciation.…”
mentioning
confidence: 99%
“…We particularly analyzed the intrinsic interactions (adult-larva and larva-larva) of Anagyrus cachamai Triapitsyn, Logarzo & Aguirre and A. lapachosus Triapitsyn, Aguirre & Logarzo (Hymenoptera: Encyrtidae), candidate agents for the neoclassical biological control of the Harrisia cactus mealybug Hypogeococcus sp. (Hemiptera: Pseudococcidae), a Brazilian native turned invasive pest of the native cacti in Puerto Rico 27 29 . With the information obtained, we predicted if both parasitoid species should be released and the level of their potential impact on the target pest.…”
Section: Introductionmentioning
confidence: 99%